2012
DOI: 10.4049/jimmunol.1101356
|View full text |Cite
|
Sign up to set email alerts
|

STAT1-Independent Control of a Neurotropic Measles Virus Challenge in Primary Neurons and Infected Mice

Abstract: Neurons are chiefly non-renewable; thus, cytolytic immune strategies to clear or control neurotropic viral infections could have lasting neurological consequences. Interferon-gamma (IFNγ) is a potent anti-viral cytokine that is critical for non-cytolytic clearance of multiple neurotropic viral infections, including measles virus (MV); however, the downstream pathways through which IFNγ functions in neurons have not been defined. Unlike most cell types studied to date in which IFNγ affects gene expression via r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(66 citation statements)
references
References 53 publications
1
62
3
Order By: Relevance
“…Noncanonically, IRF-1, -3, and -7 can upregulate ISG expression in the absence of measurable IFN (48,(79)(80)(81)(82). Utilization of noncanonical, STAT1-independent antiviral signaling by neurons has been demonstrated in neurons during measles virus, WEEV, and St. Louis encephalitis virus infection (49,83). These studies support the importance of higher levels of Irf-7 and Irf-3 to enable differentiated neurons to orchestrate a prompt and effective antiviral response.…”
Section: Figsupporting
confidence: 54%
“…Noncanonically, IRF-1, -3, and -7 can upregulate ISG expression in the absence of measurable IFN (48,(79)(80)(81)(82). Utilization of noncanonical, STAT1-independent antiviral signaling by neurons has been demonstrated in neurons during measles virus, WEEV, and St. Louis encephalitis virus infection (49,83). These studies support the importance of higher levels of Irf-7 and Irf-3 to enable differentiated neurons to orchestrate a prompt and effective antiviral response.…”
Section: Figsupporting
confidence: 54%
“…Homozygous NSE-CD46 ϩ and haplotypematched homozygous immune knockout (KO) mice were intercrossed for three or more generations to obtain NSE-CD46 ϩ mice on the desired KO background. NSE-CD46 ϩ /IFN-␥ knockout and NSE-CD46 ϩ /Stat1 knockout mice have been used in our lab previously (23,30). IFNAR1-deficient mice on a 129S2/SvPas background were obtained from Luis Sigal (Fox Chase Cancer Center, Philadelphia, PA).…”
Section: Methodsmentioning
confidence: 99%
“…During the course of previous studies, we identified numerous genes that were synthesized in primary hippocampal neurons and MEFs following IFN-␥ treatment. From this list, Bst2 was among the top 5 induced genes (23). In this study, we investigated the induction and contribution of Bst2 in MV infection of CNS neurons both in vivo and ex vivo.…”
mentioning
confidence: 99%
See 2 more Smart Citations